The Impact of Social Media on the Improvement of Mothers’ Awareness for Stunting Prevention - Lestari, Sri; Rachim, Ilmi Afrizal; Budiansyah, Andi; Dinaseviani, Anggini; Febrianda, Rendi; Romadona, Mia Rahma (Universitas Semarang, 2025)
Purpose: This study aims to provide an empirical description of a) the relationship between mothers’ maternal behaviour and awareness to improve the nutritional status of their children and families and b) their behaviour of using social media (Instagram, YouTube, Twitter and Facebook) as the primary source of information to enhance their awareness of providing balanced and nutritious foods for their children, are the subjects of this study. The purpose of this study is to provide an empirical description of both of these topics. Methods: An online questionnaire was distributed to targeted respondents, namely 133 mothers with infants and toddlers from 16 provinces in Indonesia. Regression analysis was performed using SPSS software to assess mothers' propensity in seeking information, mainly from social media, about nutritious foods when making dietary choices. Findings: This indicates a significant correlation between mothers' awareness of seeking information about nutritious food using social media and their decisions to provide daily meals and first-line complementary foods for their newborns and toddlers. However, this awareness was not related to the variety of side dishes available on the menu. Originality: This study offers original empirical evidence on the role of social media as a primary source of information for mothers in 16 Indonesian provinces, improving their awareness and decisions about nutritious feeding to prevent stunting. The study uniquely links digital engagement (social media) with improved child nutrition, addressing a gap in maternal health research in Southeast Asia.